Organisation management modern methods based on a value-oriented approach - G. N. Ryazanova (Вестник университета)
The author outlined a microeconomic agents role in the connections system in the macroeconomic space; explored the changes features in the Russian organisation at different stages of the country’s development in conjunction with changes in the values of the era; revealed the modern economic agent specifics, his worldview and value orientations; established the transformation process causal relationship of the modern economic space and the challenges facing the organisation; justified the need to take into account the stakeholder groups values in management; systematised organisation management methods based on a value-based approach. The article used evolutionary and historical, cause-and-effect research methods, the analysis and synthesis method, scientific abstraction method. The result of the study is the proposed managing methods in a modern organisation based on a value-oriented approach.